2005
DOI: 10.1186/1743-7075-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of lipid malabsorption in Cystic Fibrosis: the impact of essential fatty acids deficiency

Abstract: Transport mechanisms, whereby alimentary lipids are digested and packaged into small emulsion particles that enter intestinal cells to be translocated to the plasma in the form of chylomicrons, are impaired in cystic fibrosis. The purpose of this paper is to focus on defects that are related to intraluminal and intracellular events in this life-limiting genetic disorder. Specific evidence is presented to highlight the relationship between fat malabsorption and essential fatty acid deficiency commonly found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 260 publications
(278 reference statements)
0
17
1
5
Order By: Relevance
“…Our findings have, at least, contributed to exclude CFTR as a causative factor for defective mucosal uptake and intracellular transport of long-chain FA as well as impaired intra-enterocyte handling of lipids. Of interest, our previous studies reported the significant contribution of the permanent essential FA deficiency to CF malabsorption by interfering with intra-enterocyte lipid transport [15] , [57] .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have, at least, contributed to exclude CFTR as a causative factor for defective mucosal uptake and intracellular transport of long-chain FA as well as impaired intra-enterocyte handling of lipids. Of interest, our previous studies reported the significant contribution of the permanent essential FA deficiency to CF malabsorption by interfering with intra-enterocyte lipid transport [15] , [57] .…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient malabsorption, intestinal dysfunction, and malnutrition are among the most important and troubling early manifestations of CF. The malabsorption of fats in CF is largely due to inadequate secretion of the enzyme pancreatic lipase into the intestinal lumen, with contributions from other mechanisms 27 , resulting not only in fatty stools, but also to loss of nutritionally important dietary fat and fat-soluble vitamins. Our results suggest a model wherein excess dietary fat within the CF GI lumen also plays an indirect role in the intestinal inflammation that characterizes childhood CF GI disease by selecting for microbiota that preferentially degrade the SCFAs butyrate and propionate, important molecules for enteric health ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, intestinal epithelial cells from CF patients bearing the F508del-CFTR mutation exhibited an impressive derangement of cellular proteostasis, with OxS [ 61 ]. On the other hand, regarding the formation of intestinal lipoproteins, the literature is very poor and is limited to describing the malabsorption of fats, essentially caused by digestive defects related to pancreatic lipase, bile acids and bicarbonate [ 62 ]. The impact of CFTR deficiency on intra-enterocyte processes has been very little investigated.…”
Section: Discussionmentioning
confidence: 99%